Self-stigma in serious mental illness and autism spectrum disorder: Results from the REHABase national psychiatric rehabilitation cohort. Issue 1 (2020) - Dubreucq, J.; Plasse, J.; Gabayet, F.; Faraldo, M.; Blanc, O.; Chereau, I.; Cervello, S.; Couhet, G.; Demily, C.; Guillard-Bouhet, N.; Gouache, B.; Jaafari, N.; et al.
Abstract: Background: Self-stigma is a major issue in serious mental illness (SMI) and is negatively associated with patient outcomes. Most studies have been conducted in schizophrenia (SZ). Less is known about self-stigma in other SMI and autism spectrum disorder (ASD). The objectives of this study are: (i) to assess the frequency of self-stigma in a multicentric nonselected psychiatric rehabilitation SMI and ASD sample; and (ii) to investigate the correlates of elevated self-stigma in different SMI conditions and in ASD. Methods: A total of 738 SMI or ASD outpatients were recruited from the French National Centers of Reference for Psychiatric Rehabilitation cohort (REHABase). Evaluations included sociodemographic data, illness characteristics, and standardized scales for clinical severity, quality of life, satisfaction with life, wellbeing, personal recovery, a large cognitive battery, and daily functioning assessment. Results: 31.2% of the total sample had elevated self-stigma. The highest prevalence (43.8%) was found in borderline personality disorder and the lowest (22.2%) in ASD. In the multivariate analysis, elevated self-stigma was best predicted by early stages of personal recovery (moratorium, p = 0.001, OR = 4.0 [1.78–8.98]; awareness, p = 0.011, OR = 2.87 [1.28–6.44]), history of suicide attempt ( p = 0.001, OR = 2.27 [1.37–3.76]), insight ( p = 0.002, OR = 1.22 [1.08–1.38]), wellbeing ( p = 0.037, OR = 0.77 [0.60–0.98]), and satisfaction with interpersonal relationships ( p < 0.001, OR = 0.85 [0.78–0.93]). Conclusions: The present study has confirmed the importance of addressing self-stigma in SMI and ASD patients enrolled in psychiatric rehabilitation. The effectiveness of psychiatric rehabilitation on self-stigma and the potential mediating effects of changes in self-stigma on treatment outcomes should be further investigated.